Mechanisms of deep oil–gas accumulation: New insights from the Carboniferous Central Depression, Junggar Basin, China - Ablimiti, Yiming; He, Wenjun; Li, Na; Ma, Delong; Liu, Hailei; Bian, Baoli; Ding, Xiujian; Jiang, Mengya; Wang, Jiangtao; Cao, Jian (Frontiers in Earth Science, 2022)
To investigate the mechanisms of deep oil–gas accumulation in superimposed basins in western China, and identify deep oil–gas reserves in the Junggar Basin, this study examined Carboniferous reservoirs in the Central Depression of the basin. We determined the hydrocarbon physical properties and geochemical characteristics, and controlling factors on hydrocarbon accumulation in the deep part of the Central Depression. We present a geological model of oil–gas accumulation based on analog modeling of reservoir formation. The deep crude oil in the study area is mainly light–medium oil and wet natural gas, which were mainly derived from Permian and Carboniferous source rocks. The hydrocarbon source rocks and their thermal evolution led to hydrocarbon accumulation in the study area. Adjacent source–reservoir rocks on both sides of faults were key to vertical hydrocarbon migration and multi-stage charging. Suitable reservoir–cap rock assemblages were also important for reservoir preservation. The hydrocarbon accumulation model involves a source–reservoir link along faults, late charging, and paleo-uplifts. The reservoir types include those linked to source rocks by large-scale faults and those in paleo-uplifts surrounded by oil-generating depressions, which both have good exploration prospects. This accumulation model may be applicable to deep parts of other superimposed basins.